When equality and freedom of contract meet: a consideration of the horizontal application of the Bill of Rights - Erasmus, Andre Alexander (School For Advanced Legal Studies, 2023)
The application of human rights to private relationships is a difficult question that must be answered by all legal systems which have accepted human rights as binding upon their law. To answer this question a State has to make fundamental ideological decisions, both as to its role in society and the individual citizen's right to self-autonomy. Is law to be neutral, leaving private citizens to order their relations without intervention from the State? Or, should it play a more active transformative role by regulating and organising society to accord with a particular set of moral values and economic objectives? This dilemma is a current which runs through most contemporary moral and human rights discourse. It is not merely of abstract or academic interest. Both the reach and content of the law will be determined by which approach may prevail.